Strategic Alliance-Based Sourcing and Market Performance: Evidence from Foreign Firms Operating in China - Murray, Janet Y.; Kotabe, Masaaki; Zhou, Joe Nan (Journal of international business studies, 2005)
Although foreign multinational firms from the Triad regions increasingly use mainland China as both a sourcing and a marketing location, no study has directly examined the sourcing strategy-performance linkage. Using resource complementarity and resource dependence theory, we extend the sourcing literature and apply these perspectives to an important transitional economy-China. These two theoretical perspectives suggest that product and uncertainty factors moderate the relationship between strategic alliance-based sourcing (SA sourcing) of major components and market performance. We find that, at low levels of product innovativeness and technological uncertainty, the use of SA sourcing is positively related to market performance. However, the effects of product differentiation and demand uncertainty on the sourcing-performance relationship are insignificant.